Research on the Concentration of Companies in the Electric Power Market of Russia - Kuzmin, Evgeny A.; Volkova, Elena E.; Fomina, Alena V. (International Journal of Energy Economics and Policy, 2018)
The article is devoted to the issues of determining the structure and type of the industrial market of the Russian electric power industry. A comprehensive analysis of competition was conducted based on empirical data on installed capacities, production volumes and economic results of Russian power generating companies for 2016. The most common indices and coefficients for assessing the concentration of the industry market are critically evaluated taking into account the criteria of consistency, efficiency, intuitivity and the power of behavioral response. Based on them, a ranking approach of an integrated market type definition is proposed. The obtained results show that the Russian electricity market is classified as a diffused oligopoly with a tendency to monopolistic competition. The market is dominated by 9 significant players, who control more than 70% of electricity generation collectively. An important feature of the market is the absence of participants independent of the state and not affiliated with large industrial groups. The unclear type of the market indicates a possible change in the medium term subject to a number of conditions. This is facilitated by a stable long-term trend towards a reduction in market concentration by the Herfindahl-Hirschman index. At the same time, the probability of a significant redistribution of market shares is low until the structural problems of the industry are resolved. The revealed specificity of the industry is the existence of a significant market potential, even with a small amount of the player's market share (less than 10% sometimes). These circumstances point to the prospect of comparing the RSI residual supply indices between players in the regional market and between zones of free electricity flow in Russia. The results of the research open wide heuristic opportunities in the development of practical recommendations on the organization of corporate management and state regulation in the industry. Keywords: Market concentration, Electric power industry, Competition, Market structure. JEL Classifications: L94, D40 DOI: https://doi.org/10.32479/ijeep.7169